Optimal Allocation and Design of PSSs for Damping of Low-Frequency Oscillations in Multi-Regional Interconnected Power System - Liu, C.; Yokoyama, R.; Silva, V.R. (2005 IEEE/PES Transmission & Distribution Conference & Exposition: Asia and Pacific, 2005)
Large extended power systems are often characterized by inter-area oscillations, usually spontaneous, which may be caused by small disturbances such as changes in load that take place continually. Inter-area oscillations have been the subject for studies in fields of operation, control, and devices by many power system utilities in Japan. Power system stabilizers (PSSs) are very effective controllers in improving the damping of low-frequency oscillations, since the controllers can increase damping torque for inter area modes by introducing additional signals into the excitation controllers already equipped with generators. In this paper, allocation of multi-input PSSs in an interconnected power system with inter-area modes has been determined by an eigenvalue analysis, and PSSs for the allocated generators have been designed by a frequency response method. The designed PSSs have been verified in a Japanese power system standard model. This test system is created as a standard model based on the trunk transmission systems in the eastern area of Japan, and reflects characteristic features of the real power systems. Therefore, realistic allocation and design for enhancement of the stability of low-frequency oscillations have been verified